Pre‐transplant minimal residual disease assessment and transplant‐related factors predict the outcome of acute myeloid leukemia patients undergoing allogeneic stem cell transplantation. (12th August 2021) - Guolo, Fabio; Di Grazia, Carmen; Minetto, Paola; Raiola, Anna Maria; Clavio, Marino; Miglino, Maurizio; Tedone, Elisabetta; Contini, Paola; Mangerini, Rosa; Kunkl, Annalisa; Colombo, Nicoletta; Pugliese, Girolamo; et al.
Abstract: We studied pretransplant minimal residual disease (MRD) in 224 patients (median age 44 years; range 17‐65) with acute myeloid leukemia (AML) undergoing allogeneic stem cell transplant (HSCT) in complete remission. MRD was evaluated on marrow samples using multicolor flow cytometry and assessment of WT1 gene expression. Both methods showed a strong prognostic value and their combination allowed the identification of three groups of patients with different risk of relapse. In multivariate analysis, combined MRD was the only predictor of cumulative incidence of relapse, regardless of donor type, conditioning regimen, first or second CR at HSCT, HSCT year, and ELN risk group. Multivariate regression model showed that only negative combined MRD status ( P < .001) and myeloablative conditioning ( P = .004) were independently associated with better OS. Among MRD‐positive patients, a reduced incidence of relapse was observed in patients receiving haplo transplant ( P < .05) and in patients who showed grade II‐IV aGVHD ( P < .03). In patients with negative combined MRD, the intensity of conditioning regimen did not affect the overall favorable outcome. We suggest that pretransplant MRD evaluation combined with transplant‐related factors can identify AML patients at higher risk for relapse and might help in defining the overall transplant strategy.